Clinical Implication of Changes in Serum Cations and Anions on Clinical Severity in Sickle Cell Disease: A Case–Control Study in a Tertiary Center - Patel, Suprava; Chandrakar, Diksha; Wasnik, Preetam Narayan; Nanda, Rachita; Mohapatra, Eli (Journal of Laboratory Physicians, 2023)
Introduction Vaso-occlusive crisis in sickle cell disease (SCD) is related to disproportionate serum ions distribution. The objective was to evaluate the influence of changes in serum cations and anions on clinical severity in SCD patients.Materials and Methods The case–control study included 26 SCD cases and 27 apparently healthy control individuals. The cases were further grouped as crisis state and steady state cases. Each participant was assigned a disease severity score. All study participants were evaluated for serum electrolytes, osmolality, calcium, magnesium, phosphorus, total protein, and albumin.Results The mean serum sodium (135.65 mmol/L), chloride (99.88 mmol/L), calcium (2.28 mmol/L), magnesium (0.76 mmol/L), osmolality (285.19 mOsm/kg), and albumin (0.59 mmol/L) were grossly reduced in cases than the control group. The SCD crisis group recorded low serum sodium (p = 0.01), calcium (p = 0.011), total cations (p = 0.023), anions (p = 0.008), and cation–anion ratio (p = 0.041). Of all the cations, serum calcium correlated inversely with disease severity score (r = –0.367, p = 0.033), whereas serum albumin among the serum anions influenced severity the most (r = –0.338, p = 0.046). The cutoff values for serum calcium and albumin were, respectively, 2.41 and 0.63 mmol/L, with a sensitivity of 83.3 and 88.9%. A calculated ratio of serum sodium–albumin revealed a positive relationship with the severity score (r = 0.328, p = 0.05) with a sensitivity of 94.4% for a cutoff value of 208.45.Conclusion Low serum sodium, calcium, albumin, and raised sodium–albumin ratio were linked to the crisis state, and routine estimation of these parameters will help in the early assessment of the clinical severity and initiate appropriate fluid management.
Keywords: serum electrolytes; osmolality; crisis state; steady state; disease severity score; calcium; magnesium; albumin